Assessing Microstructure Tensile Properties Relationships in Al-7Si-Mg Alloys via Multiple Regression - Silva, Cássio; Barros, André; Vida, Talita [UNESP]; Garcia, Amauri; Cheung, Noé; Reis, Danieli A. P.; Brito, Crystopher [UNESP] (MDPI, 2022)
The development of Al-based alloys presumes a detailed understanding of the microstruc-ture evolution during solidification since the as-solidified microstructure also has effects on the subsequent thermo-mechanical processing. In the present investigation Al-7wt.%Si-xMg (x = 0.5 and 1 wt.%) alloys are subjected to transient directional solidification with a view to characterizing the microstructure evolution, with special focus on both dendritic evolution and the inherent features of the Mg2 Si and π-AlSiFeMg intermetallics. Experimental power-type functions relating the primary, secondary and tertiary interdendritic spacings to the solidification cooling rate and growth rate are developed. It is observed that the Mg content added to the Al-7wt.%Si alloy and the consequent increase in the Mg2 Si fraction tends to increase the values of the primary dendritic spacing. However, this same behavior is not verified for the growth evolution of dendritic side branches. A multiple linear regression (MLR) analysis is developed permitting quantitative correlations for the prediction of tensile properties and hardness from microstructural parameters to be established. The increase in the Mg alloy content from 0.5 to 1 was shown to promote an increase in both the ultimate tensile strength (σu) and elongation.
Keywords: Al-Si-Mg alloys; mechanical properties; microstructure; regression analysis; solidification